The relationship between nursing staff behaviour and the implementation of occupational safety and health (OSH) in the Emergency Department of Hospital X, Central Tapanuli - Pohan, Agraesta Arichdayana; Pane, Putri Yunita; Pakpahan, Eka Lolita Eliyanti (Buletin Kedokteran & Kesehatan Prima, 2025)
Hospital Occupational Health and Safety (OHS) encompasses a range of activities aimed at ensuring and protecting the safety and health of all hospital personnel, patients, patient companions, visitors, and the hospital environment. These efforts are undertaken through the prevention of workplace accidents and occupational diseases. This research aimed to analyse the relationship between nurses' behaviour and the implementation of Occupational Health and Safety (OHS) in the Emergency Department (ED) of Hospital X, Central Tapanuli, in 2025. This study employed a quantitative method with a cross-sectional design. A sample of 31 nurses participated in the research, and data were collected via questionnaires. The collected data were subsequently analysed using univariate and bivariate tests, specifically the Chi-Square test. The bivariate test results indicated a significant association between nurses' knowledge and the implementation of OHS in the ED (p-value = 0.002 < 0.05). Similarly, a significant association was found between nurses' attitudes and the implementation of OHS in the ED (p-value = 0.001 < 0.05). Based on these findings, it can be concluded that there is a relationship between the actions of nursing staff and the implementation of OHS in the ED of Hospital X, Central Tapanuli, in 2025. The implications of this research highlight the need for enhanced understanding and knowledge of OHS implementation among healthcare professionals in the ED of Hospital X, Central Tapanuli.